2009
DOI: 10.1111/j.1601-6343.2009.01465.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cortical bone thickness and root proximity at maxillary and mandibular interradicular sites for orthodontic mini‐implant placement

Abstract: Based on our results, cortical bone thickness depends on the interradicular site rather than sex or individual differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 13 publications
(17 reference statements)
5
38
0
2
Order By: Relevance
“…Cortical bone thickness varies from 0.5 to 2.5 mm in the vestibular alveolar process 5,12,13,21 , and from 1.0 to 1.5 mm in the palatal alveolar process. 22 Therefore, cortical thicknesses from 1 to 3 mm were selected to test the insertion torque of MI because cortical bone thickness is directly related to insertion torque, and insertion torque influences MI success rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cortical bone thickness varies from 0.5 to 2.5 mm in the vestibular alveolar process 5,12,13,21 , and from 1.0 to 1.5 mm in the palatal alveolar process. 22 Therefore, cortical thicknesses from 1 to 3 mm were selected to test the insertion torque of MI because cortical bone thickness is directly related to insertion torque, and insertion torque influences MI success rates.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,8,9,10,11 Some studies have assessed cortical bone thickness and bone density because they are important for the stability of MI. 12,13,14 Using microcomputed tomography, Laursen et al 15 found that the thickness of the alveolar cortical bone was often < 1.0 mm buccally and palatally in the maxilla and buccally in the anterior mandible. However, in the posterior mandible, the alveolar cortical bone was thicker than 2.0 mm.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…[1][2][3] The most used and easily accessible insertion sites are the buccal aspect of the alveolar process in both the maxilla and mandible as well as the palatal side of the maxillary alveolar process in the premolar and molar region. 4 The thickness of human cortical bone in these areas has been assessed by conventional computed tomography (CT) [5][6][7][8] and cone-beam computed tomography (CBCT). [9][10][11][12][13] More detailed information can be achieved using micro-computed tomography (micro-CT).…”
Section: Introductionmentioning
confidence: 99%
“…The failure rate is known to be more increased in the mandible compared to the maxilla. [9][10][11][12] Baumgaertel and Hans 13 and Lim et al 14 reported that the buccal cortical bone was thicker in the mandible than in the maxilla and that the buccal cortical bone thickness in the mandibular posterior area ranged from 1.50 mm to 3.65 mm. Implant site preparation, such as that associated with predrilling of the thick buccal cortical bone in the mandibular posterior area, can lower the insertion torque into the appropriate range.…”
Section: Introductionmentioning
confidence: 99%